Anonymously yours - Ferraro, Gayle; Aerial Productions (Berkeley, CA. : Berkeley Media, 2003)
An extraordinary documentary shot clandestinely in Burma, the film examines sex-trafficking in Southeast Asia through interviews with four young women. The brutal honesty of their stories exposes the commonplace bartering and selling of women and the cycles of poverty that enslave them. From the back rooms of teashops and restaurants to the lounges of five-star hotels, the Far East sex trade thrives on the routine merchandising of girls and women for the sexual pleasure of men from all cultures
Title from title screen
Editor, Keiko Deguchi ; photography, Jill Tufts ; music, Claudio Ragazzi
DVD format
Keywords: Prostitution -- Burma; Prostitution -- Southeast Asia; Child prostitution -- Burma; Prostitutes -- Burma -- Interviews